Latihan Perseptual dalam Meningkatkan Taktik dan Strategi Bermain Bulutangkis Berbasis PBA pada Atlet Pelatda Lotim - Lalu Sapta Wijaya Kusuma; Nurdin; Nazalus Sobri (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2025)
This research aims to test the effectiveness of the Perceptual training method based on Performance-Based Assessment (PBA) in improving the tactical and strategic abilities of playing badminton in East Lombok Pelatda athletes. The research method used was an experiment with a pretest-posttest design. The research subjects consisted of East Lombok Pelatda athletes who met the age criteria of 15–25 years and were active in the training program. The intervention was carried out for eight weeks, including video observations of opponents' playing patterns, match simulations, tactical discussions, and the use of auditory cues by coaches. Data is collected through performance assessments before and after the intervention using a tactics and strategy assessment rubric as well as match simulation results. The research results showed a significant increase in athletes' tactical and strategic abilities after implementing the PBA-based training method. Before the intervention, the average performance score was below 40, while after the intervention most of the subjects achieved scores above 80, even close to the maximum score of 100. The PBA approach has proven to be effective in helping athletes understand opponents' playing patterns, design strategies, and respond to match situations quickly. The stability of scores after treatment also shows that this method is able to create uniform competence among athletes with different initial characteristics. This research supports previous literature highlighting the importance of a problem-based approach in sports coaching, especially in improving tactical and strategic skills. The results provide practical guidance for coaches in designing training programs that are more effective and relevant to competition needs. Thus, integrating the PBA method into badminton training programs can be a strategic step to increase the competitiveness of athletes at regional and national levels. This research contributes both theoretically and practically to the development of sports coaching.